Personal Spaces in Public Repositories as a Facilitator for Open Educational Resource Usage - Cohen, Anat; Reisman, Sorel; Bied Sperling, Barbra (International Review of Research in Open and Distributed Learning, 2015)
Learning object repositories are a shared, open and public space; however, the possibility and ability of personal expression in an open, global, public space is crucial. The aim of this study is to explore personal spaces in a big learning object repository as a facilitator for adoption of Open Educational Resources (OERs) into teaching practices and to gain more insight into different types of OER user behaviors by analyzing the users' behaviors in the Bookmark Collection of MERLOT (a personal space, formerly known as Personal Collection), along with other community activities in that repository: writing comments and peer reviews, as well as sharing learning materials, learning exercises, and contents that were built with the content builder. In addition, using a data mining methodology, most active Bookmark Collection contributors (N=507) were classified into clusters of users with the same patterns of activity. Three clusters resulted, which gave insights into different types of contributor behavior. Furthermore, it was found that personal spaces are applicable for a variety of uses with diverse goals. Members create personal spaces for their own use, while allowing others to view and copy; or for other users. Personal space encourages the reuse of learning materials and enables the construction of unique learning processes that suit the learner's needs. They may offer the possibility of personalizing public repositories and promoting the reuse of OER.